Genomics, transcriptomics and proteomics: enabling insights into social evolution and disease challenges for managed and wild bees - Judith Trapp; Alison McAfee; Leonard J. Foster (Molecular Ecology, 2017)
Globally, there are over 20 000 bee species ( Hymenoptera: Apoidea: Anthophila ) with a host of biologically fascinating characteristics. Although they have long been studied as models for social evolution, recent challenges to bee health (mainly diseases and pesticides) have gathered the attention of both public and research communities. Genome sequences of twelve bee species are now complete or under progress, facilitating the application of additional ‘omic technologies. Here, we review recent developments in honey bee and native bee research in the genomic era. We discuss the progress in genome sequencing and functional annotation, followed by the enabled comparative genomics, proteomics and transcriptomics applications regarding social evolution and health. Finally, we end with comments on future challenges in the postgenomic era.

Dynamic properties of photosystem II membranes at physiological temperatures characterized by elastic incoherent neutron scattering. Increased flexibility associated with the inactivation of the oxygen evolving complex - Gergely Nagy; Jörg Pieper; Sashka B. Krumova; László Kovács; Marcus Trapp; Győző Garab; Judith Peters (Photosynthesis Research, 2012)